Use of Autotransfusion following Percutaneous Thrombectomy for Cardiogenic Shock Due to Pulmonary Embolism in a Single Session—A Case Report - Franz Haertel; Laura Baez; Marcus Franz; Jurgen Bogoviku; Friederike Klein; Gudrun Dannberg; P. Christian Schulze; Sven Möbius-Winkler (Diagnostics, 2023)
A 64-year-old male patient was admitted to the catheterization laboratory with a suspected myocardial infarction and in cardiogenic shock. Upon further investigation, a massive bilateral pulmonary embolism with signs of right heart dysfunction was discovered, leading to a decision to perform a direct interventional treatment with a thrombectomy device for thrombus aspiration. The procedure was successful in removing almost the entirety of the thrombotic material from the pulmonary arteries. The patient’s hemodynamics stabilized and oxygenation improved instantly. The procedure required a total of 18 aspiration cycles. Each aspiration contained approx. 60 mL blood amounting to a total of approx. 1080 mL of blood. During the procedure, a mechanical blood salvage system was used to resupply 50% of the blood via autotransfusion that would otherwise have been lost. The patient was transferred to the intensive care unit for post-interventional care and monitoring. A CT angiography of the pulmonary arteries after the procedure confirmed the presence of only minor residual thrombotic material. The patient’s clinical, ECG, echocardiographic, and laboratory parameters returned to normal or near normal ranges. The patient was discharged shortly after in stable conditions on oral anticoagulation.